2000
DOI: 10.1161/01.atv.20.7.1817
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effects of the Natural Estrogen 17β-Estradiol on Hepatic Cholesterol Metabolism in Intact Female Rats

Abstract: Abstract-The protective influence of estrogens in cardiovascular disease is believed to be partly due to beneficial effects on cholesterol metabolism. Much of the experimental data are based on models in which synthetic estrogens have been used in pharmacological doses, and therefore, the physiological role of estrogens in cholesterol metabolism is uncertain.To evaluate this important issue, we performed experiments in intact female rats with use of the natural estrogen 17␤-estradiol (E2) administered either s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 44 publications
7
20
0
4
Order By: Relevance
“…Estrogen is known to modulate several steps in cholesterol metabolism, including the activity of HMGCoA reductase, the rate-limiting enzyme in de novo cholesterol synthesis, 33,34 the expression of the LDL receptor, 35,36 as well as that of enzymes involved in liver cholesterol/bile acid excretion. 26 In the present study, HMGCoA reductase and ACAT activities were found not to be altered by invalidation of the ERa or by ACOL, pointing to pathways other than hepatic cholesterol synthesis and storage, such as increased lipoprotein or cholesterol uptake from the circulation and subsequent excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is known to modulate several steps in cholesterol metabolism, including the activity of HMGCoA reductase, the rate-limiting enzyme in de novo cholesterol synthesis, 33,34 the expression of the LDL receptor, 35,36 as well as that of enzymes involved in liver cholesterol/bile acid excretion. 26 In the present study, HMGCoA reductase and ACAT activities were found not to be altered by invalidation of the ERa or by ACOL, pointing to pathways other than hepatic cholesterol synthesis and storage, such as increased lipoprotein or cholesterol uptake from the circulation and subsequent excretion.…”
Section: Discussionmentioning
confidence: 99%
“…This hormone may influence not only cholesterol elimination but also its metabolism. These effects depends, however, on its concentration (Parini et al, 2000). The literature data provide evidence that consumption of diets containing soya protein (and phytooestrogens which are tightly associated with proteins) reduces total cholesterol and LDL-cholesterol (Carroll, 1991) and augments HDL-cholesterol (Anthony et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…37 These responses to pharmacological doses of estrogen can be abolished by simultaneous administration of antiestrogens, indicating that the effects are mediated by estrogen receptors. 38 Our results showed that the 1082G4A polymorphism in ESR2 gene influenced LDL-C and, consequently, T-chol levels only in women with abundant endogenous (premenopausal women) or exogenous estrogen levels (postmenopausal women HRT users), whereas in postmenopausal women unexposed to HRT (lower endogenous estrogen levels) no effect was observed.…”
Section: Esr2 and Pgr Variants And Lipid Levels In Women S Almeida Et Almentioning
confidence: 99%